Epistemic Virtues, Metavirtues, and Computational Complexity. - Morton, Adam (Nous (0029-4624), 2004)
The article suggests a shift in emphasis in the discussion of the internalism/externalism distinction in epistemology. Most discussions take the essential feature of states and processes susceptible to internalistic norms to be knowability—a person can know "from the inside" whether they are in the relevant states. The significance of this information is that the person can then judge and correct her reasoning in the light of what she knows about her state and her grasp of the relevant principles of rationality. But the reflections just above and elsewhere in the paper suggest that the important fact is not whether one knows what state one is in but whether one knows whether it is in accord with some inferential principle that makes it likely to result in true belief.